Confirmation of suboptimal protocols in spinal immobilisation?. Issue 12 (11th September 2015) - Dixon, Mark; O'Halloran, Joseph; Hannigan, Ailish; Keenan, Scott; Cummins, Niamh M
Abstract : Background: Spinal immobilisation during extrication of patients in road traffic collisions is routinely used despite the lack of evidence for this practice. In a previous proof of concept study (n=1), we recorded up to four times more cervical spine movement during extrication using conventional techniques than self-controlled extrication. Objective: The objective of this study was to establish, using biomechanical analysis which technique provides the minimal deviation of the cervical spine from the neutral in-line position during extrication from a vehicle in a larger sample of variable age, height and mass. Methods: A crew of two paramedics and four fire-fighters extricated 16 immobilised participants from a vehicle using six techniques for each participant. Participants were marked with biomechanical sensors and relative movement between the sensors was captured via high-speed infrared motion analysis cameras. A three-dimensional mathematical model was developed and a repeated-measures analysis of variance was used to compare movement across extrication techniques. Results: Controlled self-extrication without a collar resulted in a mean movement of 13.33° from the neutral in-line position of the cervical spine compared to a mean movement of 18.84° during one of the equipment-aided extrications. Two equipment-aided techniques had significantly higher movement (p<0.05) than other techniques. Both height (p=0.003) and mass (p=0.02) of the participants were significant independent predictors of movement. Conclusions: These data support the findings of the proof of concept study, for haemodynamically stable patients controlled self-extrication causes less movement of the cervical spine than extrications performed using traditional prehospital rescue equipment.